Low frequency energy harvesting using piezoelectric materials - Kang, Kee Yong (2015)
Vibration energy harvesting has shown potential in scavenging energy from the ambient surroundings and is very applicable especially for micro-electrical-mechanical systems or other lower power consumption devices. The feasibility of harvesting vibration energy induced by a human hand through a novel 3 cantilever design is being explored in this paper. In this design, Macro Fiber Composite (MFC) strips are subjected to a mechanical strain induced by a cantilever system under impact from the middle cantilever beam which acts as an impactor. A study was done to determine the characteristics of human hand induced vibrations as well. The results show that the vibration has a frequency range of 2 – 5.5Hz and an acceleration range of 0.5 – 5g. For these ranges, the highest root mean square power generated was 134.7μW. However, the results concluded that the use of MFC strips are not feasible when an impact mechanism is used to cause a strain in the strips due to the short operational life under such conditions.